Spanish Moth or Convict Caterpillar, Xanthopastis timais (Cramer) (Insecta: Lepidoptera: Noctiuidae) - John B. Heppner; Kathryn A. Barbara; Eileen A. Buss (EDIS)
The Spanish moth, Xanthopastis timais (Cramer), is unmistakable for any other moth in Florida. The larvae are likewise very colorful, and have been called convict caterpillars. The larvae are occasional pests of lilies, mainly in Amaryllidaceae. Spotted larval forms of Spanish moth appear similar to lily borer larvae, Brithys crini (Fabricius) (Godfrey 1972) of Europe and the Old World tropics, but only the banded larval form of the Spanish moth occurs in North America. This document is EENY-271, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2002.